Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1088/2057-1976/aae5c0
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of customizable compressive patterns to human limbs to investigate vascular reactivity

Abstract: ObjectiveCommercial devices for pneumatic compressive treatment of the limbs generally provide predefined stereotyped compressive profiles. The possibility to deliver compressive stimuli with a customizable pressure profile would be useful to differently probe the vascular reactivity to muscle compression (MC) and improve the understanding of MC-induced hyperemia. Aim of this study was the realization of a novel pneumatic system capable of generating adjustable and stable compressive conditions, preceding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Expensive professional machines are generally adopted to the purpose of eliciting rapid tissue compressions [13]. We faced this need when investigating the muscular and skin reactivity to compressive stimuli [14,15], and developed a custom system on the basis of PC-driven valves for controlled rapid inflation and deflation of the cuff [14,16], as recently reviewed [17]. For the present application, a single 3-way valve was adopted for both inflation and deflation.…”
Section: Discussionmentioning
confidence: 99%
“…Expensive professional machines are generally adopted to the purpose of eliciting rapid tissue compressions [13]. We faced this need when investigating the muscular and skin reactivity to compressive stimuli [14,15], and developed a custom system on the basis of PC-driven valves for controlled rapid inflation and deflation of the cuff [14,16], as recently reviewed [17]. For the present application, a single 3-way valve was adopted for both inflation and deflation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides therapeutic treatments, IPC devices can be effectively used to examine in-depth vascular phenomena as hyperemia. Ferraresi et al [11] presented the design and modeling of an IPC device aimed at providing customizable pressure profiles to human limbs, whereas Messere et al [12,13] showed applications of such device on a set of healthy subjects, aimed at developing protocols for the study of the mechanisms behind hyperemia (i.e., the local increase of blood flow to tissues). The device, shown in Fig.…”
Section: Ipc Device For the Study Of Vascular Phenomenamentioning
confidence: 99%
“…Resistance vessels in skeletal muscle exhibit a rapid dilatation in response to mechanical stimuli, such as short-lasting external compressions, whose underlying mechanisms are still unclear. Messere et al [12] performed an analysis on 10 healthy volunteers with the IPC device described in the previous section. The subjects sat on a chair with a backrest, the leg fully extended with the cuff wrapped distally to the knee.…”
Section: Investigation Of Vascular Reactivity To Mechanical Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the limits of commercial devices, a novel pneumo-tronic device based on the application of defined pressure patterns to the limb of a subject with high dynamic performance, so as to allow the investigation of vascular phenomena with appropriate accuracy and precision, has been designed and is presented in this paper. A general description of the device architecture has been already presented in [23], in which the Authors focused on a clinical application concerning the study of vascular reactivity to an external compression exerted by a pressure-controlled pneumatic cuff. A preliminary characterization of the system has been presented in [24], considering only a limited working condition (step pressure reference signal, 50 mmHg of amplitude).…”
mentioning
confidence: 99%